Evaluating wait times from screening to breast cancer diagnosis among women undergoing organised assessment vs usual care - Chiarelli, Anna M (Br J Cancer, 2017)
BACKGROUND: Timely coordinated diagnostic assessment following an abnormal screening mammogram reduces patient anxiety and may optimise breast cancer prognosis. Since 1998, the Ontario Breast Screening Program (OBSP) has offered organised assessment through Breast Assessment Centres (BACs). For OBSP women seen at a BAC, an abnormal mammogram is followed by coordinated referrals through the use of navigators for further imaging, biopsy, and surgical consultation as indicated. For OBSP women seen through usual care (UC), further diagnostic imaging is arranged directly from the screening centre and/or through their physician; results must be communicated to the physician who is then responsible for arranging any necessary biopsy and/or surgical consultation. This study aims to evaluate factors associated with diagnostic wait times for women undergoing assessment through BAC and UC. METHODS: Of the 2 147 257 women aged 50–69 years screened in the OBSP between 1 January 2002 and 31 December 2009, 155 866 (7.3%) had an abnormal mammogram. A retrospective design identified two concurrent cohorts of women diagnosed with screen-detected breast cancer at a BAC (n=4217; 47%) and UC (n=4827; 53%). Multivariable logistic regression analyses examined associations between wait times and assessment and prognostic characteristics by pathway. A two-sided 5% significance level was used. RESULTS: Screened women with breast cancer were two times more likely to be diagnosed within 7 weeks when assessed through a BAC vs UC (OR=1.91, 95% CI=1.73–2.10). In addition, compared with UC, women assessed through a BAC were significantly more likely to have their first assessment procedure within 3 weeks of their abnormal mammogram (OR=1.25, 95% CI=1.12–1.39), ⩽3 assessment procedures (OR=1.54, 95% CI=1.41–1.69), ⩽2 assessment visits (OR=1.86, 95% CI=1.70–2.05), and ⩾2 procedures per visit (OR=1.41, 95% CI=1.28–1.55). Women diagnosed through a BAC were also more likely than those in UC to have imaging (OR=1.99, 95% CI=1.44–2.75) or a biopsy (OR=3.69, 95% CI=2.64–5.15) vs consultation only at their first assessment visit, and two times more likely to have a core or FNA biopsy than a surgical biopsy (OR=2.08, 95% CI=1.81–2.40). Having ⩽2 assessment visits was more likely to reduce time to diagnosis for women assessed through a BAC compared with UC (BAC OR=10.58, 95% CI=8.96–12.50; UC OR=4.47, 95% CI=3.94–5.07), as was having ⩽3 assessment procedures (BAC OR=4.97, 95% CI=4.26–5.79; UC OR=2.95, 95% CI=2.61–3.33). Income quintile affected wait times only in women diagnosed in UC, with those in the two highest quintiles more likely to receive a diagnosis in 7 weeks. CONCLUSIONS: Women with screen-detected breast cancer in OBSP were more likely to have shorter wait times if they were diagnosed through organised assessment. This might be as a result of women diagnosed through a BAC having more procedures per visit, procedures scheduled in shorter intervals, and imaging or biopsy on their first visit. Given the significant improvement in timeliness to diagnosis, women with abnormal mammograms should be managed through organised assessment.